Prototype internal target design for storage ring experiments. (26th November 2015) - Petridis, N; Grisenti, R E; Litvinov, Yu A; Stöhlker, Th
Abstract: The introduction of cryogenically cooled, few micrometer-sized nozzle geometries and an essential modification of the experimental storage ring (ESR) target station allowed for a reliable operation using low- Z gases at target area densities in the range of 10 13 –10 14 cm −2 . Therefore, a remarkably versatile target source was established, enabling operation over the whole range of desired target gases (from H2 to Xe) and area densities (∼10 10 to ∼10 14 cm −2 ). Moreover, the considerably smaller orifice diameter of the new target source enables a much more compact inlet chamber while, at the same time, maintaining the demanding vacuum requirements of a storage ring. A completely new inlet chamber design is presented here, which, besides the improvements regarding the achievable area densities, will feature a variable beam width down to 1 mm at the ion beam interaction region. This is of paramount importance with respect to the realization of high precision experiments, e.g. by reducing the inaccuracy of the observation angle causing the relativistic Doppler broadening. While being intended for the deployment at the future high energy storage ring within the SPARC collaboration, the new inlet chamber can also replace the current one at the ESR or serve as an internal target for CRYRING.